Síntesis y comentario bíblico a la encíclica Spe salvi - Caballero, José Antonio (Veritas, 2008)
The Encyclical Letter Spe salvi follows the same trend as other preceding writings by Pope Benedict XVI: proclaiming Christ. This essay starts with a synthesis of the Encyclical Letter as an answer to the question about the kind of Hope taught by Christianity. Then, this article tries to offer an overview of the Biblical concept of Hope. Finally, we comment the Nos. 27, 49-50, trying to limit itself, even if not all exclusively, to the allusions made to the fourth Gospel.